An Optimal Culture Medium for Laccase Production and Sugar Cane Vinasse Biotreatment with Trametes villosa Using Plackett-Burman and Central Composite Designs - Caballero, Rosa Elena; Jiménez, Víctor; Miranda, Mónica; Rovira, Dalys; Branda, Guillermo; Ramos Chue de Pérez, Juana (Applied Environmental Research, 2024)
The optimal conditions for laccase production and vinasse biotreatment with a native strain of Trametes villosa were determined by a screening-optimization approach. Eleven factors including nutrient concentration, vinasse dilution (%v/v), inoculum volume, carbon to nitrogen ratio and initial pH, were investigated for their effects on laccase activity applying the Plackett-Burman screening design. The selected factors were optimized using a central composite design, and then evaluated on a vinasse biotreatment experiment. The factors that contributed the most to the enzymatic activity were the concentrations of MgSO4∙7H2O (A), FeSO4∙7H2O (B) and CuSO4∙5H2O (C), alongside initial pH. After 10 days, laccase activity was 544.038 U L-1 for the following concentrations of A, B and C: 0.250 g L-1, 0.020 mg L-1, and 0.100 g L-1, respectively. Vinasse biotreatment under optimized conditions resulted in 82.74%, 78% and 75.97% of phenol, color, and COD removal respectively, while final pH value was 6.90. These results showed that the native strain of T. villosa has a good potential for further research on laccase production and vinasse sustainable management.